Incorporation of Active Metal Species in Crystalline Porous Materials for Highly Efficient Synergetic Catalysis. Issue 22 (5th November 2020) - Cui, Wen‐Gang; Hu, Tong‐Liang
Abstract: The design and development of efficient catalytic materials with synergistic catalytic sites always has long been known to be a thrilling and very dynamic research field. Crystalline porous materials (CPMs) mainly including metal–organic frameworks and zeolites with high scientific and industrial impact have recently been the subject of extensive research due to their essential role in modern chemical industrial processes. The rational incorporation of guest species in CPMs can synergize the respective strengths of these components and allow them to collaborate with each other for synergistic catalysis, leading to enhanced catalytic activity, selectivity, and stability in a broad range of catalytic processes. In this review, the recent advances in the development of CPMs‐confined active metal species, including metal nanoparticles, metal/metal oxides heteroparticles, metal oxide, subnanometric metal clusters, and polyoxometalates, for heterogeneous catalysis, with a particular focus on synergistic effects between active components that result in an enhanced performance are highlighted. Insights into catalysts design strategies, host–guest interactions, and structure–property relationships have been illustrated in detail. Finally, the existing challenges and possible development directions in CPMs‐based encapsulation‐structured synergistic catalysts are discussed. Abstract : Incorporation of active metal species in crystalline porous materials (CPMs) can synergize the respective strengths and allow them to collaborate with each other for synergistic catalysis. In this review, the state‐of‐the art progress in the encapsulation of catalytically active metal species by CPMs as well as their synergy functions for enhanced catalytic performance is summarized in detail.